2018
DOI: 10.1002/cphc.201701198
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐Cortex Microglia‐Derived Exosomes: Nanoparticles for Glioma Therapy

Abstract: The function and integrity of the nervous system require interactive exchanges among neurons and glial cells. Exosomes and other extracellular vesicles (EVs) are emerging as a key mediator of intercellular communication, capable of transferring nucleic acids, proteins and lipids influencing numerous functional and pathological aspects of both donor and recipient cells. The immune response mediated by microglia-derived exosomes is most prominently involved in the spread of neuroinflammation, neurodegenerative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 35 publications
0
38
0
1
Order By: Relevance
“…Indeed, these results positioned the MScCM treatment on the level of cell based therapy, where similar beneficial outcomes were observed [ 15 , 20 ]. The next step of this project will be isolation of the microvesicles (exosomes) from the MScCM as novel therapeutic agents as we recently demonstrated for microglia cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these results positioned the MScCM treatment on the level of cell based therapy, where similar beneficial outcomes were observed [ 15 , 20 ]. The next step of this project will be isolation of the microvesicles (exosomes) from the MScCM as novel therapeutic agents as we recently demonstrated for microglia cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the crosstalk between GAMs in glioma, it is also important to highlight that recent studies showed that microglia-derived exosomes in the brain could be used as nanotherapeutic agents against glioma cells ( Murgoci et al, 2018 ). In fact, extracellular ATP promotes microglia activation and induces the release of EVs, which can potentially mediate intercellular communication between microglia and the microenvironment ( Drago et al, 2017 ).…”
Section: Microglia and Astrocytes’ Role In Glioblastoma Malignancymentioning
confidence: 99%
“…283,284 It is reported that inhibition of NF-κB pathway activation is involved in breaking cellular redox homeostasis and triggers ROS production and accumulation through the JNK-mitogen-activated protein kinase (MAPK) axis. 285,286 Due to high specificity and the power to cross the BBB, exosome-and nanovesicle-mediated delivery [287][288][289] of peptides, [290][291][292][293] small molecules, miRNA, [294][295][296] and other drugs in Fig. 3 Steps of focal cerebral ischemia development…”
Section: Therapeutic Approaches For Ischemia and Gliomamentioning
confidence: 99%